SPECIFICITY OF THE SPACE AND TIME IN M. Y. LERMONTOV'S NOVEL ART - V. M. Gryaznova; Y. S. Shvetsova (Гуманитарные и юридические исследования)
The present article is focused on the representation of chronotopic (space-time) categories in the lyrical-psychological novel by M. Y. Lermontov «A Hero of Our Time». Individually-author's presentations about the space and time form an original model of the novelist's artistic reality. The vast variety of the novel's spatio-temporal relations takes a form of the theoretical and ideological self-awareness by main characters which try to find their own place and purpose in the world.